Factors that influence students’ memorization in the superior Tahfidz program to improve Islamic character - Nofiaturrahmah , Fifi; Khamdanah, Umi (Proceeding International Conference on Religion, Science and Education, 2025)
Instilling a love of the Koran in students and forming individuals with Koranic character can be done through the use of superior tahfidz activities. Students not only develop their morals, but also get used to getting closer to Allah SWT. It is a good effort and noble deed that was highly recommended by the Prophet, and one way to preserve the Koran is by memorizing it. Because, maintaining the purity of memory is one of the reasons why memorizing the Koran is valuable. Based on the results of observations made by researchers, MI Al-Islam Dempet has a good program, namely the superior Tahfidz program. The habit of memorizing juz amma every morning where students gather in the tahfidz classroom, each student memorizes before starting to memorize it to pray together and murajaah. The aim of this researcher is to analyze the factors that influence students’ memorization in the superior Tahfidz program to improve Islamic character at the Madrasah Ibtidaiyah Al-Islam Dempet. This research uses a qualitative research approach with the type of field research (Field research). To obtain valid data, in this study researchers collected data using three techniques, namely, interviews, observation and documentation. Researchers use credibility criteria (degree of trust), test the validity of the data using extended observation techniques, increase persistence, member check, triangulation and data reduction, data presentation and verification of the collected data. Based on the research results, it can be concluded that: Factors that influence memorization activities include intention or determination, forgetting to bring juz amma’, attention from parents, class conditions during the activity, methods used, appropriate student and teacher recitation activities in competency area.